Exploring The Impact of Incentives, Work Flexibility, And Workplace Safety on Job Satisfaction: A Case Study of Shopeefood Drivers in Denpasar City - Natasia, Natasia; Rismawan, Putu Agus Eka; Diputra, I Komang Suryadnya (EMAS: Jurnal Ekonomi, Manajemen dan Bisnis, 2026)
In an era of competition in the digital service sector, drivers of application-based food delivery services must continuously improve their performance to maintain service quality and company competitiveness. One way to maintain and improve performance is to evaluate factors influencing driver job satisfaction so that human resource management can be carried out more optimally. This study aims to determine the effects of incentives, work flexibility, and work safety on the job satisfaction of ShopeeFood drivers in Denpasar City. A quantitative approach with a survey technique was used for the research method. The study sample consisted of all 70 ShopeeFood drivers in Denpasar City using a total sampling method. Research data were collected via questionnaires and analyzed using multiple linear regression. The results showed that incentives have a positive and significant effect on driver job satisfaction, indicating that fair and proportional incentives can increase satisfaction. Work flexibility also positively and significantly affects job satisfaction, suggesting that the freedom to manage work time provides drivers with comfort. Additionally, work safety positively and significantly affects driver job satisfaction. Therefore, implementing an appropriate incentive system, providing adequate work flexibility, and ensuring work safety guarantees can increase the job satisfaction of ShopeeFood drivers in Denpasar.